Advances in stromal cell therapy for management of Alzheimer’s disease - Srivastava, Rashi; Li, Aidong; Datta, Tirtharaj; Jha, Niraj Kumar; Talukder, Salehikram; Jha, Saurabh Kumar; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Deposition of misfolded proteins and synaptic failure affects the brain in Alzheimer’s disease. Its progression results in amnesia and cognitive impairment. Absence of treatment is due to excessive loss of neurons in the patients and the delayed effects of drugs. The enhanced pluripotency, proliferation, differentiation, and recombination characteristics of stromal cells into nerve cells and glial cells present them as a potential treatment for Alzheimer’s disease (AD). Successful evidence of action in animal models along with positive results in preclinical studies further encourage its utilization for AD treatment. With regard to humans, cell replacement therapy involving mesenchymal stromal cells, induced-pluripotent stromal cells, human embryonic stromal cells, and neural stems show promising results in clinical trials. However, further research is required prior to its use as stromal cell therapy in AD related disorders. The current review deals with the mechanism of development of anomalies such as Alzheimer’s and the prospective applications of stromal cells for treatment.